Peran Perempuan Dalam Pelestarian Lingkungan di Desa Wisata Tegalmengkeb Kabupaten Tabanan Bali (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
Women and nature are a unity that cannot be separated. The three main figures in environmental preservation in Tegalmengkeb Village, namely Bunda, Mama Eca, and Mbok Aniek, have become women's real roles in carrying out environmental preservation activities. Theory of Ecofeminism by Vandana Shiva (2005) as a scalpel to analyze the role of women in environmental conservation in Tegalmengkeb Village, Tabanan Regency, Bali. The subsistence perspective in Vandana Shiva's terminology is an alternative to prevent environmental damage from increasing in industrial society, the market economy, or patriarchal capitalism. Bunda, Mama Eca, and Mbok Aniek are carrying out environmental conservation activities consisting of turtle conservation, animal shelters, tree planting, and communal forests based on concerns arising from the current ecosystem imbalance. These environmental conservation activities have been successfully carried out without eliminating social systems, livelihoods, and technology and have become a part of the village's tourist attractions.